2022
DOI: 10.1371/journal.pone.0277839
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life and associated factors among cancer patients in Ethiopia: Systematic review and meta-analysis

Abstract: Introduction Cancer is the main cause of morbidity and mortality in every part of the world, regardless of human development. Cancer patients exhibit a wide range of signs and symptoms. Being diagnosed with cancer has a variety of consequences that can affect one’s quality of life. The term "health-related quality of life" refers to a multidimensional concept that encompasses a person’s whole health. The availability of data on the prevalence of poor quality of life among cancer patients in Ethiopia is critica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 32 publications
0
4
1
Order By: Relevance
“…A similar recent study conducted in the cancer centers of Amhara Regional State also reported a higher average QoL score of 44.32 ( 19 ). The mean score of the QoL of patients with cancer in this study was also much lower than the national pooled result of various studies in Ethiopia, which was 57.91 ( 30 ). Nonetheless, these Ethiopian studies reported significantly lower mean QoL summary scores compared to a study conducted in Sweden.…”
Section: Discussioncontrasting
confidence: 78%
“…A similar recent study conducted in the cancer centers of Amhara Regional State also reported a higher average QoL score of 44.32 ( 19 ). The mean score of the QoL of patients with cancer in this study was also much lower than the national pooled result of various studies in Ethiopia, which was 57.91 ( 30 ). Nonetheless, these Ethiopian studies reported significantly lower mean QoL summary scores compared to a study conducted in Sweden.…”
Section: Discussioncontrasting
confidence: 78%
“…A study showed that patients with early‐stage disease had a better HRQoL than advanced‐stage esophageal cancer patients 52 . An Ethiopian review reported the metastatic stage and low income level as determinants of poor HRQoL in cancer patients 53 . Hence, it is crucial to implement vigilant monitoring and promptly initiate the most effective treatment approaches for patients with comorbidities and advanced‐stage gastrointestinal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…27 , 29 , 42–44 The multidimensional nature of the predictors identified is consistent with the multidimensional nature of the concept of QoL, which refers to physical, mental, and social dimensions. 15 , 16 …”
Section: Discussionmentioning
confidence: 99%
“…27,29,[42][43][44] The multidimensional nature of the predictors identified is consistent with the multidimensional nature of the concept of QoL, which refers to physical, mental, and social dimensions. 15,16 Finally, all the studies focusing on non-adherence considered adherence to endocrine therapy. These medicines are often taken orally, generally for five to ten years, thus charging the burden of their correct and regular assumption on the patients themselves.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation